THE LEGEND OF WA WULAMONIANDWA MATAIN MUNA ETHNIC - Bayana, Bayana; Kuasa Baka, Wa; Sahidin, La Ode (Universitas Halu Oleo, 2020)
The aim of this research was to explain the meaning contained in the Wa Wulamoni and Wa Mata Legends in the Muna Ethnic, as well as to explain the values contained in the Wa Wulamoni and Wa Mata Legends in the Muna Ethnic.The theory used was the thought of Roland Barthes about Semiotics and Clyde Kluckhohn's thinking about Cultural Values. The method used in the research was qualitative descriptive. Data Sources in the research were Wa Wulamoni and Wa Mata legends that were extracted or taken from informants. Data collection techniques in this research were direct observation, recording and quotation.The data in this research were analyzed using descriptive analytics. The results of the analysis can be concluded that the meanings contained in Wa WulamoniLegenddescribe social life of the Muna ethnic, such as glorifying a woman, the Patience Test, persevering and describing the traditions of the Muna ethnic community, namely the traditions of kaghomboand marriage, whereas the meaning of Wa Mata legend, namely: Ethics or behavior of child care in the family, respect for women, and discordant marriages. The values contained in the Wa Wulamoni and Wa Mata Legends, namely: Economic values that describe the economic system of the Lamaeo Village community, moral values that describe habits in everyday life, and religious values that describe the belief system in Muna ethnic especially in the community of Lamaeo and Lakarinta villages.Â Keywords: Meaning, value, legend, Muna ethnic